2017
DOI: 10.2298/hemind160421046m
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dextransucrase from Leuconostoc mesenteroides T3, water kefir grains isolate

Abstract: The production of dextransucrase (DS) by Leuconostoc mesenteroides T3, novel isolate from water kefir grain, was studied and optimized. Bacterial supernatant reached activity of 3.1 U/ml when the culture was grown at 23 °C and under static culture condition using classical Tsuchiya medium for DS production. The increase of sucrose concentration to 7% led to an increase of DS activity by 52% compared to the control. Medium with 2% beef extract and 1% yeast extract resulted in 4.52 U/ml, which was 47% higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Some other authors have reported 180 rpm, 150 rpm and 200 rpm (Dols et al, 1998;Honorato and Rodrigues, 2010;Sawale and Lele, 2010a) for the production of dextransucrase. Contrary to above given results, L. mesenteroides T3 gave best results (3.1 U/mL) at static condition in the recent report (Miljkovic et al, 2017).…”
Section: Optimization Of Agitation Ratecontrasting
confidence: 87%
See 3 more Smart Citations
“…Some other authors have reported 180 rpm, 150 rpm and 200 rpm (Dols et al, 1998;Honorato and Rodrigues, 2010;Sawale and Lele, 2010a) for the production of dextransucrase. Contrary to above given results, L. mesenteroides T3 gave best results (3.1 U/mL) at static condition in the recent report (Miljkovic et al, 2017).…”
Section: Optimization Of Agitation Ratecontrasting
confidence: 87%
“…Whereas, L. mesenteroides PCSIR-3 and L. mesenteroides CMG713 dextransucrase gave best result at 26 °C and 30 o C, respectively with enzyme activity of 0.23 U/mL and 0.67 U/mL, respectively (Ul Qader et al, 2001;Sarwat et al, 2008). In the recent study, maximum activity of L. mesenteroides T3 dextransucrase (3.10 U/ml) was obtained at 23 °C (Miljkovic et al, 2017). …”
Section: Optimization Of Incubation Temperaturementioning
confidence: 89%
See 2 more Smart Citations
“…Lactic acid bacteria have a long history of safe use in human consumption and, therefore, among variety of microorganisms, are most widely explored for the production of microbial exopolysaccharides (Nikolic et al, 2012). Fermentation processes for EPS production are quite expensive due to purification costs, giving an advantage to the use of enzymes (Miljkovic et al, 2017). Dextran, being an extensively important microbial exopolysaccharide is synthesized from sucrose by the aid of dextransucrase enzyme.…”
Section: Introductionmentioning
confidence: 99%